Effect of NT-proBNP on Serum Calcium: A Longitudinal Analysis - Maria Rita Stancanelli; Giuseppe Restivo; Thea Corriere; Carmela Cannarozzo; Maria Gabriella Ferrara; Rosario Salemi; Maria Eva Sberna; Angelo Iraci; Ada Restivo; Valeria Furia; Elisa Longhitano; Domenico Santoro; et al. (Medicina)
Background and Objectives: Brain natriuretic peptide (NT-proBNP) is a biomarker widely used in diagnosing and monitoring heart failure. Its impact on electrolyte homeostasis is known, particularly for sodium. However, its relationship with serum calcium remains unclear. This retrospective observational study aimed to investigate the longitudinal association between NT-proBNP and serum calcium levels in a cohort of hospitalized patients with the goal of determining whether NT-proBNP could have a direct or indirect impact on calcium metabolism. Materials and Methods: We included 688 patients with 1022 repeated measurements of NT-proBNP and serum calcium collected during hospitalization from March 2022 to February 2025. Linear mixed models (LMMs) were employed to analyze longitudinal associations, adjusting for age, eGFR, estimated plasma volume status (ePVs), CRP, potassium, and albumin. Results: Baseline analysis revealed a negative correlation between NT-proBNP and serum calcium (r = −0.23, p < 0.001). Univariate LMM demonstrated a significant negative association (β = −1.3 × 10−5, p < 0.001), which remained significant in multivariate analysis (β = −6.9 × 10−6, p = 0.01), accounting for intrasubject variability. This suggests that as NT-proBNP increases, serum calcium levels decrease within individual patients, independent of confounders. This study’s findings indicate that NT-proBNP may influence calcium excretion, possibly through mechanisms involving the sodium–calcium exchanger (NCX) in renal tubules, similar to its effects on sodium homeostasis. Conclusions: This is the first study to evaluate the longitudinal impact of NT-proBNP on serum calcium, highlighting a potential clinical relevance in patients with cardiac dysfunction. Limitations include a retrospective design and a lack of urine calcium data. Further research is warranted to validate these findings and elucidate the underlying mechanisms.